2015
DOI: 10.1507/endocrj.ej15-0083
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic appearance of focal Hashimoto’s thyroiditis: A single institution experience

Abstract: HasHimoto's tHyroiditis (HT), which is characterized by a firm, painless goiter and the presence of high serum thyroid antibody, is the most common type of chronic autoimmune thyroiditis. Up to 10 times more common among women than men, the disease affects one-to-two percent of Caucasian women, with peak incidence between the ages of 30 and 50 years [1]. During progression of autoimmune thyroiditis, changes in ultrasonographic (US) findings are very variable, reflecting the dynamic nature of diseases and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Increased vascularity on color power Doppler is more likely to be seen in focal thyroiditis. 4,16 Yildiz et al 15 found no lesions located in the upper pole of the thyroid gland, ten lesions in the mid portion (91%), and one lesion in the lower pole. In our study, the majority of the lesions were also located in mid portion (n=30, 83%).…”
Section: Discussionmentioning
confidence: 98%
“…Increased vascularity on color power Doppler is more likely to be seen in focal thyroiditis. 4,16 Yildiz et al 15 found no lesions located in the upper pole of the thyroid gland, ten lesions in the mid portion (91%), and one lesion in the lower pole. In our study, the majority of the lesions were also located in mid portion (n=30, 83%).…”
Section: Discussionmentioning
confidence: 98%